IS THE TABOO OF FEMALE SEXUALITY THE SOLE REASON FOR THE CONTINUATION OF FEMALE GENITAL MUTILATION IN EGYPT? - Tabi Stew (al-Afkar, Journal For Islamic Studies, 2019)
As the first conviction of FGM in the U.K. proves, female genital mutilation is a ‘harmful cultural practice’ that persists across the world. Egypt has one of the highest rates of FGM in the world. Based on a variety of different studies and questionnaires undertaken in doctors’ surgeries and hospitals across the country, three clear reasons are given for the continuation of the practice. These are the belief that it is decreed by Islam, that it is a tradition and to preserve young women’s chastity as it would reduce their sexual desire. The overarching theme of these justifications is the fear and control of female sexuality, given the teachings of modesty in the Qur’an and the importance of chastity in order to obtain a good marriage in Egyptian society. However, the Qur’an does not condone female genital mutilation or mention it. Additionally, the Qur’an promotes sexual fulfilment and positivity within the confines of marriage for both men and women which directly conflicts with the consequences of FGM. The importance of honour and the preservation of chastity in Egyptian society continues to prevail in modern Egyptian society, and medicalisation legitimises the practice among the educated elite. However, this work hopes to prove that certain interpretations of certain aspects of the Qur’an and the hadith and Sunnah have led to the need to control female sexuality, and these beliefs are intertwined with tradition and result in the continuation of female genital mutilation in Egypt.